Local Charge Distribution Engineered by Schottky Heterojunctions toward Urea Electrolysis. Issue 27 (8th August 2018) - Li, Caicai; Liu, Youwen; Zhuo, Zhiwen; Ju, Huanxin; Li, Dian; Guo, Yanpeng; Wu, Xiaojun; Li, Huiqiao; Zhai, Tianyou
Abstract: Urea electrooxidation with favorable thermodynamic potential offers great promise for decoupling H2 /O2 evolution from sluggish water splitting, and simultaneously mitigating the problem of urea‐rich water pollution. However, the intrinsically slow kinetics of the six‐electron transfer process impels one to explore efficient catalysts in order to enable widespread use of this catalytic system. In response, taking CoS2 /MoS2 Schottky heterojunctions as the proof‐of‐concept paradigm, a catalytic model to modulate the surface charge distribution for synergistically facilitating the adsorption and fracture of chemical group in urea molecule is proposed and the mechanism of urea electrooxidation at the molecular level is elucidated. Based on density functional calculations, the self‐driven charge transfer across CoS2 /MoS2 heterointerface would induce the formation of local electrophilic/nucleophilic region, which will intelligently adsorb electron‐donating/electron‐withdrawing groups in urea molecule, activate the chemical bonds, and thus trigger the decomposition of urea. Benefiting from the regulation of local charge distribution, the constructed Schottky catalyst of CoS2 ‐MoS2 exhibits superior urea catalytic activities with a potential of 1.29 V (only 0.06 V higher than the thermodynamic voltage of water decomposition) to attain 10 mA cm −2 as well as robust durability over 60 h. This innovational manipulation of charge distribution via Schottky heterojunction provides a model in exploring other highly efficient electrocatalysts. Abstract : The Schottky heterojunction formed between semiconductive MoS2 and metallic CoS2 would induce the formation of electrophilic and nucleophilic regions on CoS2 and MoS2, respectively. When urea oxidation reaction occurs, owing to electrostatic interactions, carbonyl and amino groups will be intensively absorbed on different sites. As a result, the interaction between CoS2 and MoS2 will definitely promote the decomposition of urea.